The activation of the G-protein-coupled estrogen receptor promotes the aggressiveness of MDA-MB231 cells by targeting the IRE1α/TXNIP pathway - Maryam Mohammad-Sadeghipour; Mohammad Hadi Nematollahi; Hassan Ahmadinia; Mohammad Reza Hajizadeh; Mehdi Mahmoodi (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: This study investigated modulating the G protein-coupled estrogen receptor (GPER) on the IRElα/TXNIP pathway and its role in drug resistance in MDA-MB231 cells. Experimental approach: To determine the optimal concentrations of G1 and 4-hydroxytamoxifen (TAM), GPER expression and ERK1/2 phosphorylation were analyzed using qRT-PCR and western blotting, respectively. Cells were treated with individual concentrations of G1 (1000 nM), G15 (1000 nM), and TAM (2000 nM), as well as combinations of these treatments (G1 + G15, TAM + G15, and G1 + TAM) for 24 and 48 h. The expression levels of GPER, IRE1α, miR-17-5p, TXNIP, ABCB1, and ABCC1 genes and TXNIP protein expression were evaluated. Finally, apoptosis and cell migration were examined using flow cytometry and the wound-healing assay, respectively. Findings/Results: Activating GPER with its specific agonist G1 and TAM significantly increased IRE1α levels in MDA-MB231 cells. IRE1α through splicing XBP1 led to unfolded protein response. In addition, decreased TXNIP gene and protein expression reduced apoptosis, increased migration, and upregulated the genes associated with drug resistance. Conclusion and implication: Our investigation revealed that blocking the GPER/IRE1α/TXNIP pathway in MDA-MB231 cells could enhance treatment efficacy and improve chemotherapy responsiveness. The distinct unfolded protein response observed in MDA-MB231 cells may stem from the unique characteristics of these cells, which lack receptors for estrogen, progesterone, and HER2/neu hormones, possessing only the GPER receptor (ER-/PR-/HER2-/GPER+). This study introduced a new pathway in TNBC cells, indicating that targeting GPER could be crucial in comprehensive therapeutic strategies in TNBC cells.